Three dimensional alginate-fucoidan composite hydrogel augments the chondrogenic differentiation of mesenchymal stromal cells. (20th August 2016) - Karunanithi, Puvanan; Murali, Malliga Raman; Samuel, Shani; Raghavendran, Hanumanantha Rao Balaji; Abbas, Azlina Amir; Kamarul, Tunku
Highlights: Fucoidan increased cell proliferation and gene expression of chondrogenic markers. Fucoidan significantly enhanced GAG synthesis and accumulation. Incorporation of fucoidan delayed the transition of hMSCs to the hypertrophic state. This biomimetic composite scaffold can be used for cartilage repair based therapies. Abstract: Presence of sulfated polysaccharides like heparan sulphate has often been implicated in the regulation of chondrogenesis. However, recently there has been a plethora of interest in the use of non-animal extracted analogs of heparan sulphate. Here we remodeled alginate (1.5%) by incorporating fucoidan (0.5%), a natural sulphated polysaccharide extracted from seaweeds to form a composite hydrogel (Al-Fu), capable of enhancing chondrogenesis of human mesenchymal stromal cells (hMSCs). We confirmed the efficiency of fucoidan incorporation by FTIR and EDX analysis. Further, its ability to support hMSC attachment and chondrogenic differentiation was confirmed by SEM, biochemical glycosaminoglycan quantification, real-time quantitative PCR and immunocytochemical analyses of chondrogenic markers Sox-9, Collagen II, Aggrecan and COMP. Effect of Al-Fu hydrogel on hMSC hypertrophy was also confirmed by the downregulation of hypertrophic genes Collagen X and Runx2. This composite scaffold can hence be used as a cartilage biomimetic biomaterial to drive hMSC chondrogenesis and for other cartilage repair based therapies.